Progressão da escoliose neuromuscular e opção cirúrgica na encefalopatia crônica não progressiva infantil: uma revisão de escopo - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2023)
Objective: To carry out a systematic review of the progression of scoliosis in patients with cerebral palsy. Methods: Systematic review study with searches for journals in the PubMed database from September to December 2020 with specific descriptors associated with the Boolean operator "or" "longitudinal" or "cohort" or "control-case" and "prospective" and " cerebral palsy" and "scoliosis" or "spine deformity" or "spinal deformity" or "neuromuscular". Eligibility criteria for inclusion and exclusion of studies were applied, with subsequent data tabulation. Results: A total of 986 articles were found, only six articles were eligible for desired data extraction after applying eligibility criteria. Conclusion: Age and Gross Motor Function Classification System (GMFCS) can be clinical predictors of scoliosis progression. Scoliosis was more progressive in patients with GMFCS III, IV and V. Patients with a smaller Cobb angle during the bone growth period have a lower chance of curve progression.
Keywords: Escoliose; Paralisia Cerebral; Criança; Adolescente; CIENCIAS DA SAUDE; Coluna vertebral - Anomalias; Crianças com paralisia cerebral; Crianças com deficiências do desenvolvimento